Fields of authority : special purpose governance in Ontario, 1815-2015 - Lucas, Jack, 1987- (Institute of Public Administration of Canada series in public management and governance., 2016)
"Everywhere we turn in Canadian local politics--from policing to transit, education to public health, planning to utilities--we encounter a peculiar institutional animal: the special purpose body. These "ABCs" of local government--library boards, school boards, transit authorities, and many others--provide vital public services, spend large sums of public money, and raise important questions about local democratic accountability. In Fields of Authority, Jack Lucas provides the first systematic exploration of local special purpose bodies in Ontario. Drawing on extensive research in local and provincial archives, Lucas uses a "policy fields" approach to explain how these local bodies in Ontario have developed from the nineteenth century to the present. A lively and accessible study, Fields of Authority, will appeal to readers interested in Canadian political history, urban politics, and urban public policy."--